ARDUINO BABY MONITORING WITH TELEGRAM BOT AND WIFI CONNECTION - Muhammad Daffa Akbari; Rusdianto Roestam (IT for Society, 2019)
The rapid growth of technology has brought the basic needs of human to become easier to be fulfilled. Moreover, in this globalization era, the use of Smartphone and Internet of Things (IOT) has become common things in daily life. This advancement in technology could be applied in accommodating people’s necessity. One of the common cases to be found nearby is on how parents could keep their eyes on their children; which could be lacked at times. Sometimes, the children could be out of the parents’ reach, especially when it comes to the need of working on daily chores. This research study aims to facilitate the problem faced by most parents in monitoring their children: within the use of technology to monitor the children’s activity. This research brought the centralized Wi-Fi network using Telegram application on smartphone which provide automated system that will automatically send notification when the children is crossing their safety line. All system requirements needs to be identified first before planning, design, and developing system. Conducting test will be the last step to make sure the system is working properly.